Rubens's Dying Seneca and Masculinity - Hults, Linda C. (The sixteenth century journal, 2018)
This essay reconstructs the reception of Rubens's moving painting of Seneca's death (ca. 1615, Alte Pinakothek, Munich), based on Tacitus's narrative in the Annals, by men who were its likely target audience: educated professionals influenced by Neostoicism and Justus Lipsius's works. Although both art historians and classicists have discussed this work for its illumination of Rubens's context and the early modern reception of Seneca and Tacitus, its gendered aspects invite more scrutiny. Drawing from feminist theory, masculinity studies, and gender-focused scholarship on both ancient Rome and early modern Europe, this study suggests how Rubens's painting inspired a male audience aspiring to autonomy and transcendence, while implicitly excluding women from those possibilities. Thus, the early modern affinity with the Roman world, exemplified brilliantly by Rubens as a humanist and artist, and particularly evident in The Dying Seneca, carried with it the continuation of Roman attitudes toward gender.